The effect of supplementing different levels of fenugreek seeds (Trigonella foenum – graecum) on physiological performance of Japanese quail (Cutornix-cutornix japonica) exposed to oxidative stress induced by hydrogen peroxide - Taha, Ahmed T; AL Douri, Ahmed A (Pharmacognosy Communications)
Background: Fenugreek seed (Trigonella feonum graecum) was evaluated for its effects on physiological performance and antioxidant status in Japanese quail (Cutornix-cutornix japonica). In this trial 5 or 10 g of fenugreek seeds/kg diet were feed to birds in two replicated pens (five bird/cage) per treatment starting at 18 weeks of age. Two treatment were given standard diet and with or without H2O2 in the drinking water (T1 and T2) Another two treatments were supplemented with 5 or 10 g fenugreek ground seed/kg diet (T3 and T4) and 0.5% H2O2 in drinking water, A further two treatments were supplemented 5 or 10 g fenugreek grounded seeds/kg diet and without any addition to the drinking water (T5 and T6).The present study has shown that there was a significant decline in the malondialdihyde (MDA) and an increase in the glutathione (GSH) concentration in the liver tissue in the birds treatment with both ground fenugreek seed levels (5 and 10/kg diet). The fenugreek treated birds showed a significant difference to the control group (p < 0.05) for the birds treated with H2O2. The results also indicated to enhanced antioxidants levels (as determined by GSH concentration) in birds treated with H2O2 when supplemented with fenugreek seeds (5 or 10 g/kg diet). We also report a significant (p < 0.05) increase in RBC and Hb concentration and a difference to the control group decrease in the WBC, glucose, cholesterol levels as well as the and aspartate aminotransferase (AST) and alanine aminotransferase (ALT) enzymes activities in blood serum in birds treated with both fenugreek seeds levels compared with control groups (T1 and T2).The results suggest that fenugreek seeds supplementation at 5 or 10 gm/kg diet may enhance antioxidant status in Japanese quail.
Keywords: Fenugreek; Japanese quail; oxidative stress; hydrogen peroxide; enzymes